The Shift in the Concept of Liability for Medical Negligence After the Enactment of the 2023 Health Law - Dhanudibroto, Handojo; Widjaja, Gunawan (International Journal of Social Service and Research, 2025)
This study aims to examine the shift in the concept of imposing responsibility for medical negligence losses in the past to the present. From the review of the Supreme Court's decision regarding the imposition of liability for losses for medical negligence until the issuance of Law No. 17 of 2023 concerning Health, it was found that there was a shift in the concept of imposing liability for losses caused by medical and health workers. This shift in concept occurred because the use of civil law as a reference for the imposition of losses became irrelevant with the birth of health law in 2023. In the past, the concept of imposing medical negligence losses used the concepts of vicarious liability and responded liability, which later changed to the concept of ostensible liability where the characteristics are different from the previous two concepts. The use of the concept of ostensible liability is relevant as the basis for imposing liability for losses incurred by medical personnel who practice independently. The research method used is normative legal research where research is carried out on legal norms, rules, jurisprudence and principles in laws and regulations (statute approach) with the aim of analyzing the harmony of norms and providing legal arguments or finding legal concepts of liability and losses.